Presentation Quality of Financial Reports - Nurmiati; Fina Diana; Iswandy Roi Pandapotan Simbolon (IECON: International Economics and Business Conference, 2024)
This study investigates the elements that affect the quality of financial report presentation of state-owned firms, particularly PT. PLN (Persero). The purpose of this study is to examine the impact of human resource competency and Enterprise Resources Planning (ERP) elements on the caliber of financial report presentation at PT PLN (Persero) Sulawesi Expense Management Center Distribution Unit (UIP3B). 51 employees that utilize ERP PT PLN (Persero) (UIP3B) Sulawesi were given questionnaires to complete as part of the quantitative research strategy. The multiple linear regression approach is used for data analysis in this study. The findings of the study indicate that whereas human resource competency has a favorable and considerable impact on the quality of financial report presentation, ERP has no effect at all. Nonetheless, the quality of financial report presentation is positively and significantly impacted by both ERP and human resource capability at the same time. Because staff are still learning how to utilize ERP, research indicates that it has little impact on the caliber of financial report presentation. The suggestions made are meant to assist PLN management in creating an ERP application training program that is simpler to execute.